Using the mind map method in medical education, its advantages and challenges: A systematic review - Atiyeh Sadat Sajadi; Alireza Babajani; Shahnam Sedigh Maroufi; Nazanin Sarraf (Journal of Education and Health Promotion)
Mind mapping stands as a contemporary approach to education, introducing an innovative means of teaching and learning. In current times, this technique is embraced due to its ability to enhance the learning and retention process. This investigation explored the imperative nature of adopting novel educational methodologies such as mind mapping, while also examining its benefits and constraints. During the timeframe spanning from 2000 to 2023, the terms “mind map,” “medical education,” and “thinking skills” were employed as keywords to conduct searches across nine databases: PubMed, Cochrane, Web of Sciences, Science Direct, ProQuest, CNHL, Springer, Wiley, and Google Scholar. After conducting searches across the aforementioned databases, a total of 63 articles were retrieved. Following the elimination of duplicated entries and articles that did not align with the predefined inclusion criteria, the examination focused on 10 relevant articles. This analysis adhered to the guidelines outlined by the Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA) protocol, available at www.prisma-statement.org. The examination revealed a multitude of notable advantages associated with the implementation of mind maps which are classified into three groups (Enhancing Memory and Comprehension, Fostering Intellectual Growth, Streamlining Learning and Teaching). Additionally, two challenges of the studies were mentioned. Considering the positive ratio of merits to challenges, it is anticipated that this educational methodology will be increasingly incorporated into medical education, owing to its paramount importance and potential.